Effect of meteorological events on flood occurrence in Batman, Turkey - Sunkar, Murat; Tonbul, Saadettin (My University, 2011)
The purpose of this study is to evaluate the effect of meteorological events on the occurrence of floods in Batman in the southeastern Anatolia Region of Turkey. Batman is an urban area, which has a high risk of floods due to its location along the stream bed of Iluh Creek. No recent flood or torrent event in this area has caused as much damage as that on October 31-November 1, 2006, which caused 10 deaths in the city center in addition to material damage of 15 million Euros. The total amount of precipitation on October 31 is measured as 30 mm with a total of 57 mm precipitation on the next day giving rise to a catastrophic flood occurrence. The daily maximum precipitation of 57 mm is not the highest recorded; a precipitation value of 69.2 mm is measured in April 1999. Intense precipitation in Batman on October 31 and November 1, 2006 fell in these two days of a one-week rainy period. One week of rainfall on the ground causes a decrease in the water absorption capacity of the soil. In such an environment, almost all of the 16 mm rainfall that fell within 15 minutes on October 31 became runoff and led to the flood event. The exceedance probability of this rainfall, with an intensity of 10.6, is 2.43%. In order to determine the effect of meteorological events on the occurrence of such a catastrophe, annual, daily and within-the-day intense rainfalls are analyzed systematically. Besides meteorological conditions, the encroachment of stream beds by urbanization and industry compounds the loss of life and property.
Keywords: Anatolia; Batman; Turkey; absorption; catastrophic event; flood; measurement method; meteorology; precipitation intensity; rainfall; risk assessment; runoff; urban area; urbanization